Gene expression patterns of Sirtuin family members (SIRT1 TO SIRT7): Insights into pathogenesis and prognostic of Myelodysplastic neoplasm - Goes, João Vitor Caetano (2024)
To assess and validate the gene expression profile of SIRTs (SIRT1, SIRT2, SIRT3, SIRT4, SIRT5, SIRT6, and SIRT7) in relation to the pathogenesis and prognostic progression of Myelodysplastic neoplasm (MDS). Eighty bone marrow samples of patients with de novo MDS were diagnosed according to WHO 2022 and IPSS-R criteria. Ten bone marrow samples were obtained from elderly healthy volunteers and used as control samples. Gene expression levels of all SIRTs were assessed using RT-qPCR assays. Downregulation of SIRT2 (p = 0.009), SIRT3 (p = 0.048), SIRT4 (p = 0.049), SIRT5 (p = 0.046), SIRT6 (p = 0.043), and SIRT7 (p = 0.047) was identified in MDS patients compared to control individuals. Also, we identified that while SIRT2-7 genes are typically down-regulated in MDS patients compared to normal controls, there are relative expression variations among MDS patient subgroups. Specifically, SIRT4 (p = 0.029) showed increased expression in patients aged 60 or above, and both SIRT2 (p = 0.016) and SIRT3 (p = 0.036) were upregulated in patients with hemoglobin levels below 8 g/dL. SIRT2 (p = 0.045) and SIRT3 (p = 0.033) were highly expressed in patients with chromosomal abnormalities. Different SIRTs exhibited altered expression patterns concerning specific MDS clinical and prognostic characteristics. The downregulation in SIRTs genes (e.g., SIRT2 to SIRT7) expression in Brazilian MDS patients highlights their role in the disease's development. The upregulation of SIRT2 and SIRT3 in severe anemia patients suggests a potential link to manage iron overload-related complications in transfusion-dependent patients. Moreover, the association of SIRT2/SIRT3 with genomic instability and their role in MDS progression signify promising areas for future research and therapeutic targets. These findings underscore the importance of SIRT family in understanding and addressing MDS, offering novel clinical, prognostic, and therapeutic insights for patients with this condition.